Translation of IRF-1 Restricts Hepatic Interleukin-7 Production to Types I and II Interferons: Implications for Hepatic Immunity - Rueschenbaum, Sabrina; Cai, Chengcong; Schmidt, Matthias; Schwarzkopf, Katharina; Dittmer, Ulf; Zeuzem, Stefan; Welsch, Christoph; Lange, Christian M. (Frontiers in Immunology, 2021)
Interleukin-7 (IL-7) is a non-redundant cytokine with crucial pro-survival functions in the adaptive immune system. Yet, little is known on the role of IL-7 in innate immunity. In the present study, the impact of hepatic IL-7 on innate immune cells was assessed by functional experiments as well as in patients with compensated or decompensated liver cirrhosis or acute-on-chronic liver failure (ACLF). Human hepatocytes and liver sinusoidal endothelial cells secreted IL-7 in response to stimulation with type I and II, but not type III interferons (IFNs). De novo translation of interferon-response factor-1 (IRF-1) restricted IL-7 production to stimulation with type I and II IFNs. LPS-primed human macrophages were identified as innate immune target cells responding to IL-7 signaling by inactivation of Glycogen synthase kinase-3 (GSK3). IL-7-mediated GSK3 inactivation augmented LPS-induced secretion of pro-inflammatory cytokines and blunted LPS tolerance of macrophages. The IFN-IRF-1-IL-7 axis was present in patients with liver cirrhosis. However, patients with liver cirrhosis with or without ACLF had significantly lower serum concentrations of IL-7 compared to healthy controls, which may contribute to LPS-tolerance in these patients. In conclusion, we propose the presence of a pro-inflammatory cascade in which type I / II IFNs induce hepatic IL-7 in an IRF-1-restriced manner. Beyond its role in adaptive immune responses, IL-7 appears to augment the response of macrophages to LPS and to ameliorate LPS tolerance, which may improve innate immune responses against invading pathogens.